Sensitivity and Antibiotic Resistance of Aeromonas spp. Isolated from Some Fish ‎Farms in Basrah, Iraq - Al-Shammari, Sabah Mahmood Hamad (University of Thi-Qar Journal of agricultural research, 2024)
This study sought to isolate and identify ‎Aeromonas species and assess their antibiotic ‎resistance. The inquiry centered on 56 dubious fish contaminated with Aeromonas germs from ‎Basra. The fish weighed between 20 and 44 grams and were thereafter placed in individual ‎tanks. This research was undertaken at the Fish Breeding and Nutrition Laboratory within Fish and Marine Resources, College of Agriculture, University of Basra. Specimens were obtained from the ulcerated dermal regions, ‎kidneys, liver, and spleen. A homogenous bacterial isolation was subsequently conducted and ‎confirmed leading to identification of Gram-negative bacteria. ID-GN demonstrated that ‎clinical isolates, including ‎‎‎A. hydrophila, ‎A. sobria, and ‎‎A. caviae, aligned with the ‎fundamental biochemical assays and employed by Vitec 2. The Clinical and Laboratory Standards Institute (CLSI, 2021) was used to evaluate the antibiotic susceptibility of Aeromonas isolates responsible for carp infections using the Kirby-Bauer disk diffusion method. ‎We are looking at how resistant three types of bacteria are to oxytetracycline, erythromycin and ampicillin after exposed to them. The results ‎show differing levels of resistance to various antibiotics ‎A. hydrophila has an 11% resistance to ‎oxytetracycline, 33% to erythromycin and a significant 95% to ampicillin. ‎A. sobria exhibits a ‎‎10% resistance to oxytetracycline, 45% to erythromycin and 75% resistance to ampicillin. A. ‎caviae shows 8% resistance to oxytetracycline, 50% to erythromycin and 77% resistance to ‎ampicillin. The mean antimicrobial resistance (MAR) for three ‎Aeromonas species studied is ‎around 80 percent to ampicillin with moderate resistance to erythromycin observed in fifty ‎percent of cases. Oxytetracycline demonstrates the greatest sensitivity and a low resistance rate ‎of ten percent among the isolates.